4x-1(3+5x)=2(x-1)+1

Simple and best practice solution for 4x-1(3+5x)=2(x-1)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-1(3+5x)=2(x-1)+1 equation:



4x-1(3+5x)=2(x-1)+1
We move all terms to the left:
4x-1(3+5x)-(2(x-1)+1)=0
We add all the numbers together, and all the variables
4x-1(5x+3)-(2(x-1)+1)=0
We calculate terms in parentheses: -(2(x-1)+1), so:
2(x-1)+1
We multiply parentheses
2x-2+1
We add all the numbers together, and all the variables
2x-1
Back to the equation:
-(2x-1)
We get rid of parentheses
4x-1(5x+3)-2x+1=0
We add all the numbers together, and all the variables
2x-1(5x+3)+1=0
We move all terms containing x to the left, all other terms to the right
2x-1(5x+3)=-1

See similar equations:

| -(x+5)=13+8x | | h-185=433 | | F(x)=5(x-3)+17 | | 5x+12+7x=180  | | -3x+8=-4(x-1) | | 7w=4w+27 | | 3x+8=3x+7x | | 3.72=6.08+a | | 32+7x=8(8x+4) | | 8/9-w=1/4 | | -5+v=6 | | 40+k=3(5-8k) | | 4.6=z+5.4 | | 5(2x+8)=-27+7 | | -3(3-2n)=-25+4n | | 2(5x+7)=-48+42 | | 6-x=-15.3 | | -4(7+6n)-6n=-4n+24 | | -4y=-48 | | -1.5-z=3.0 | | (8y-64)=180 | | -5n=-(6n-4) | | -x/4-5=18 | | 10=5.6+n | | -(v+6)=-6v-11 | | 23.00+53.00=24.75x+17.25 | | x-2.78=-3.0 | | 7v-9=2(v-7) | | -5/8=a-3 | | -1(v+6)=-6v-11 | | −3(4x+5)+4x+1=-30−30 | | 5.3+x=-7.4 |

Equations solver categories